ANALYSIS OF SURGICAL INTERVENTIONS FOR PELVIC FLOOR PROLAPSE: A FIVE-YEAR OBSERVATIONAL EXPERIENCE - Yuldashev S.K. (Central Asian Journal of Medicine, 2025)
Pelvic organ prolapse (POP) surgery is regarded as a functional surgical approach aimed at restoring pelvic anatomy and alleviating associated symptoms that significantly impact patients’ quality of life. Over the past decades, prolapse surgery has undergone substantial evolution, shaped by advances in surgical techniques and shifts in clinical preferences. With the rise of evidence-based medicine, many traditional practices have been re-evaluated, and contemporary studies continue to validate or challenge the efficacy of various operative strategies. Understanding the relative advantages and limitations of these procedures is essential for guiding clinical decision-making and optimizing patient outcomes. This study presents a five-year retrospective analysis of prolapse surgeries performed by gynecologists across regional branches in the Republic. It assesses the distribution of surgical methods employed, evaluates alignment with current clinical guidelines, and highlights gaps in procedural adoption, particularly regarding uterus-preserving techniques and apical support methods. The findings offer a valuable overview of prevailing surgical trends and underscore the need for broader dissemination of modern urogynecological approaches within local practice settings.